Introduction to Global Military History : 1775 to the Present Day - Black, Jeremy, 1955- (New York Routledge Taylor & Francis, 2013)
This textbook for all students of modern military history uses case studies, chapter introductions and up-to-date research and covers all aspects of the major modern conflicts.
Includes Bibliography and Index.
Keywords: Military History, Modern